The effect of democracy and corruption paradox on economic growth: MINT countries - Tutuncu, Asiye; Bayraktar, Yasar (Springer Science and Business Media LLC, 2024)
AbstractThis study examines the impact of democracy and corruption on the economic growth of Mexico, Indonesia, Nigeria, and Turkey over the 1975–2022 period. Utilizing the Fractional Frequency Flexible Fourier Panel Cointegration and Dynamic Ordinary Least Squares coefficient estimator, two models are employed to test hypotheses regarding economic growth. The findings reveal that democracy plays an upgrading role in the economic growth of all MINT countries, while the effect of corruption varies. In Indonesia and Mexico, corruption has a positive impact on growth, reflecting the effect of democracy, whereas Nigeria and Turkey experience a negative impact. The democracy model supports the compatibility hypothesis for all countries, asserting a positive link between democracy and economic growth. However, the corruption model yields divergent results, with Nigeria and Turkey aligning with the “grease in the wheels” hypothesis, implying that corruption can facilitate economic growth by bypassing bureaucratic obstacles, while Indonesia and Mexico support the "sand in the wheels" hypothesis, indicating that corruption hinders economic growth. This highlights the need for governments to strengthen institutions through transparency, accountability, and credibility via robust oversight and governance mechanisms. Therefore, democratic advancement, streamlined bureaucracy, and anti-corruption policies are imperative for sustainable economic growth and welfare.
Keywords: CAH15-02-01 - economics; 8. Economic growth; 1. No poverty; 16. Peace & justice